The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3991/ijim.v14i04.12759
|View full text |Cite
|
Sign up to set email alerts
|

Developing English Learning Materials for Mechanical Engineering Students Using Padlet

Abstract: Due to emergence of English for Specific Purposes where nowadays English not only a learning material for students but it has become a need for people. Mechanical Engineering graduates are expected to have English ability to compete in job profession. For that reason, it was important to develop English learning material based on the needs of Mechanical Engineering student. The aimed of this research was to develop appropriate English learning materials for the students of Mechanical Engineering Students by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Hence, Petkovska (2015) states that the lecturers have to be more creative in offering learning materials that contribute to the advancement, which will be an essential reference for universities. Etfita & Wahyuni (2020) state that a rising number of research projects provide English for specific purposes courses to satisfy the expansion of students' needs from different aspects. Those researches indicate the change in educational study, especially English, for specific purposes that have been reported in the context of technological growth.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Petkovska (2015) states that the lecturers have to be more creative in offering learning materials that contribute to the advancement, which will be an essential reference for universities. Etfita & Wahyuni (2020) state that a rising number of research projects provide English for specific purposes courses to satisfy the expansion of students' needs from different aspects. Those researches indicate the change in educational study, especially English, for specific purposes that have been reported in the context of technological growth.…”
Section: Introductionmentioning
confidence: 99%
“…The material chosen for the EAP courses should be consistent with the course's objectives (Kohnke, 2019). Therefore, it should meet the goals and be acceptable in terms of the language standard, quality, and suitability (Etfita & Wahyuni, 2020;Yundayani et al, 2019).…”
Section: The Outcomes Of the Students' Needs Analysis Of Ewapmentioning
confidence: 99%
“…As modern science and technology are advancing, people's interaction and communication are globalized, in this context, as the lingua franca, English learning and English communication have become a part of many people's daily life [1][2][3][4]. Our society needs talents that excel in English-Chinese translation and English education.…”
Section: Introductionmentioning
confidence: 99%